Working Families: Age, Gender and Daily Survival in Industrializing Montreal - Bradbury, Bettina (Labour / Le travail, 1994)
Keywords: Famille; Femmes

The Working-Class Family Economy: Montreal, 1861-1881 - Bradbury, Bettina (Université Concordia, 1984)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

Surviving as a Widow in 19th - Century Montreal - Bradbury, Bettina (Urban History Review / Revue d'histoire urbaine, 1989)
Keywords: Famille; Femmes; Veuvage

Working Families: Age, Gender, and Daily Survival in Industrializing Montreal - Bradbury, Bettina (McClelland & Stewart, 1993)
Keywords: Famille; Femmes

Class, Culture, Family and the Law: Wife to Widow in Nineteenth-Century Quebec - Bradbury, Bettina (Programme d'études sur le Québec de l'Université McGill, 1997)
Keywords: Femmes; Mariage; Veuvage

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Histoire sociale / Social History, 1984)
Keywords: Famille; Femmes; Travail

Pigs, Cows, and Boarders: Non-Wage Forms of Survival among Montreal Families, 1861-91 - Bradbury, Bettina (Labour / Le travail, 1984)
Keywords: Famille; Femmes

Mourir chrétiennement: La vie et la mort dans les établissements catholiques pour personnes âgées à Montréal au XIXe siècle - Bradbury, Bettina (Revue d'histoire de l'Amérique française, 1992)
Keywords: Communautés religieuses; Hospices; Hôpitaux; Mortalité; Soeurs Grises; Soeurs de la Providence

MOLSON, ANNE - Bradbury, Bettina (Dictionnaire biographique du Canada, 1990)

Debating Dower: Patriarchy, Capitalism and Widows' Rights in Lower Canada» - Bradbury, Bettina (Power, Place and Identity: Historical Studies of Social and Legal Regulation in Quebec, 1998)
Keywords: Femmes; Mariage; Veuvage

Familles ouvrières à Montréal. Âge, genre et survie quotidienne pendant la phase d’industrialisation - Bradbury, Bettina (Boréal, 1995)
Keywords: Alimentation; Famille; Logement; Vêtements

Women and Technological Change in Nineteenth Century Montreal - Bradbury, Bettina (Women, Work and Place, 1994)
Keywords: Femmes

The Fragmented Family: Family Strategies in the Face of Death, Illness, and Poverty, Montreal, 1860-1885 - Bradbury, Bettina (Family Bonds and Gender Divisions: Readings in the Sociology of the Family, 1988)
Keywords: Famille; Orphelinats

The Fragmented Family: Family Strategies in the Face of Death, Illness, and Poverty, Montreal, 1860-1885 - Bradbury, Bettina (Childhood and Family in Canadian History, 1982)
Keywords: Famille; Orphelinats

Pigs, Cows and Boarders. Non-wage forms of Survival among Montreal Families, 1861-1881 - Bradbury, Bettina (The Challenge of Modernity: A Reader in Post-Confederation Canada, 1992)
Keywords: Famille; Femmes

The Fragmented Family: Family Strategies in the Face of Death, Illness and Poverty, Montreal, 1860-1885 - Bradbury, Bettina (Family Patterns, Gender Relations, 1993)
Keywords: Famille; Orphelinats

Women and Wage Labour in a Period of Transition, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1987)
Keywords: Famille; Femmes; Travail

Elderly Inmates and Care Giving Sisters: Catholic Institutions for the Elderly in Nineteenth Century Montreal - Bradbury, Bettina (On the Case: Explorations in Social History, 1998)
Keywords: Communautés religieuses; Hospices; Hôpitaux; Mortalité; Soeurs Grises; Soeurs de la Providence

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1994)
NOTICE DG
Keywords: Famille; Femmes; Travail

Property and Marriage: the Law and the Practice in Early Nineteenth-Century Montreal - Bradbury, Bettina; Stewart, Alan; Kolish, Evelyn; Gossage, Peter (Histoire sociale / Social History, 1993)
Keywords: Droit; Mariage

Marriage Contracts as a Source for Historians - M. Stewart, Alan; Bradbury, Bettina (Class, Gender and the Law in Eighteenth and Nineteenth Century Quebec: Sources and Perspectives, 1993)
Keywords: Mariage